2018
DOI: 10.1159/000489932
|View full text |Cite
|
Sign up to set email alerts
|

Methodologic Assessment of the Systematic Reviews of Ophthalmic Adverse Drug Reactions Published in Ophthalmology Journals: A Systematic Review

Abstract: Purpose: This systematic review aims to characterize and review the methodology of the systematic reviews reporting ophthalmic adverse drug reactions. Methods: This systematic review followed the Cochrane Collaboration and the Preferred Reporting Items for Systematic Reviews and Meta-analyses guide. MEDLINE and EMBASE databases were searched, by all Ophthalmology journals. All systematic reviews reporting ophthalmic adverse drug reactions in the last decade were included. Data on methodology were extracted. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…In most of the studies, only a small proportion has good reporting [2325]. In a previous work, we analyzed the methodology used in systematic reviews reporting ophthalmic adverse drug reactions and found the same methodological issues [26]. In 2016, the PRISMA group developed guidance to help reporting systematic reviews of adverse drug reactions, the PRISMA Harms [11].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies, only a small proportion has good reporting [2325]. In a previous work, we analyzed the methodology used in systematic reviews reporting ophthalmic adverse drug reactions and found the same methodological issues [26]. In 2016, the PRISMA group developed guidance to help reporting systematic reviews of adverse drug reactions, the PRISMA Harms [11].…”
Section: Discussionmentioning
confidence: 99%